Pengaruh Penggunaan Fitur Shopee Pay Terhadap Perilaku Konsumsi Islam - Muhamad Rifki Botutihe; Aldiwanto Landali (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the effect of using the shopeepay feature on Islamic consumption behavior in the people of Gorontalo. Exogenous variables in this study, namely convenience, safety, and lifestyle and endogenous variables, namely, Islamic consumption behavior. The research method used is quantitative with multiple linear regression analysis data using EViews 12 Software. The results show that the convenience of the shopeepay feature has a positive and significant effect on Islamic consumption behavior, the safety of the shopeepay feature does not have a significant effect on Islamic consumption behavior, lifestyle has a significant effect on consumption behavior Islam.